2008
DOI: 10.1292/jvms.70.1253
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Uterine Receptor mRNAs for Oxytocin and Estrogen in the Pseudopregnant Rat

Abstract: ABSTRACT. This study examined the uterine oxytocin-(OTR) and estrogen-(ER) receptor mRNA levels during and after pseudopregnancy (PSP) in rats. An increased OTR mRNA level was observed from day 14 of PSP, and the maximal level was attained during the following proestrus. The levels of ERα mRNA were low during PSP and significantly increased during the following estrus. The level of ERβ mRNA was significantly decreased during proestrus and then returned to the values observed during days 7-14 of PSP by estrus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Pseudopregnancy was induced in Sprague Dawley female rats by mating with male rats two weeks after vasectomy, and mating was confirmed by checking for a vaginal plug (day 1 of pseudopregnancy) [23,24]. These were no fertilized eggs in the vaginas of the pseudopregnant rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudopregnancy was induced in Sprague Dawley female rats by mating with male rats two weeks after vasectomy, and mating was confirmed by checking for a vaginal plug (day 1 of pseudopregnancy) [23,24]. These were no fertilized eggs in the vaginas of the pseudopregnant rats.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that only the state of endometrial receptivity or dormant blastocysts did not increase the expression of let-7a. Let-7a expression was significantly induced by the process of embryo invasion, implying that let-7a may participate in endometrial decidualization.To further explore whether let-7a expression is associated with the induction of implantation, we tested the effects of pseudopregnancy, experimentally induced decidualization and delayed implantation.Pseudopregnancy was induced in Sprague Dawley female rats by mating with male rats two weeks after vasectomy, and mating was confirmed by checking for a vaginal plug (day 1 of pseudopregnancy) [23,24]. These were no fertilized eggs in the vaginas of the pseudopregnant rats.…”
mentioning
confidence: 99%